Work Environment and Compensation on Nurse’s Job Satisfaction and Its Implication on Extra Role Behavior in Efarina Etaham Hospital, Purwakarta - Bertie Riyestavani; Yusuf Arifin (Faculty of Economics and Business, University of Pasundan, 2016)
This study aims to obtain empirical evidence about the effect of work environment and the compensation on nurse‘s job satisfaction and its implications on extra role behavior in Efarina Etaham Hospital, Purwakarta. The method used was descriptive and verificative analysis. The data collection was an interview by using a questionnaire along with observation techniques. The population is 70 nurses. Field data collection was conducted in 2014. Data were analyzed by path analysis. The results showed that work environment, compensation, job satisfaction, and extra role behaviors generally are relatively good. Meanwhile, the work environment and compensation partially and simultaneously have a positive and significant effect on job satisfaction. Job Satisfaction has positive and significant effect on extra role behaviour of nurses.